GIS based study on liquefaction-induced soil subsidence, a case from Urayasu area, Chiba, Japan - Pokhrel, Rama Mohan; Kiyota, Takashi (Journal of Nepal Geological Society, 2016)
Urayasu City in Chiba prefecture, Japan, which is composed of young reclaimed land. Following the 2011 off the Pacific Coast of Tohoku Earthquake (M=9), severe liquefaction-induced ground subsidence was extensively observed in this young filled land. The major problems associated with liquefaction and ground subsidence like tilting of houses, buckling of roads and lifelines cut off were commonly observed. Therefore, a detailed study on possibility and amount of ground subsidence is essential to carry out in such area. In this paper, a variation of ground subsidence is studied after severe liquefaction takes place in an earthquake. Randomly distributed borehole locations were selected and calculated the liquefaction potential for each boreholes. Geostatistical method of interpolation a kriging method was applied to attain a spatial variation of liquefaction potential within the area by using selected borehole locations. The ground subsidence was estimated by using airborne LiDAR (Light Detection and Ranging) images before and after the earthquake which gives the spatial distribution of soil subsidence map. The liquefaction potential value was picked up from the liquefaction potential distribution map and the subsidence value of the corresponding points were picked up from the ground subsidence map. By comparing these two values the relationship between liquefaction potential and ground subsidence has been developed.